KESESUAIAN PUTUSAN HAKIM DILIHAT BERDASARKAN SYARAT PERJANJIAN - Janice Vianney; Gunawan Djajaputra (Jurnal Hukum Adigama, 2022)
As a rule of law, all behavior and behavior of society is regulated by law and law has the highest position in the state. The formation of these written regulations aims to regulate people's behavior in order to create order and legal certainty, where it is hoped that there will be no violation of the rights and obligations of everyone. The term regarding legal subjects comes from the Dutch language recht subject which is generally interpreted as supporting rights and obligations, namely humans and legal entities. In social activities, people (person) and legal entity (recht person) as legal subjects often intersect with agreements. It can be concluded that base on Article 1313 of the Civil Code, “An agreement is an act by which one person or more binds himself to one or more other people”. The purpose of the agreement is to meet the needs and gain profit. Based on the research results, it can be concluded that the purpose of an agreement is contained in the contents of the agreement itself. A new agreement can be said to be a valid agreement if it fulfills the requirements for the validity of the agreement set forth in Article 1320 of the Civil Code.